Ocular Trauma During COVID-19 Pandemic: A Systematic Review and Meta-analysis. Issue 5 (2nd September 2022) - Liang, Huiyu; Zhang, Meiqin; Chen, Man; Lin, Timothy P.H.; Lai, Mingying; Chen, Haoyu
Abstract : Purpose: This study aimed to summarize the latest literature on the trends and incidence of ocular trauma during the COVID-19 pandemic. Design: Systematic review and meta-analysis. Methods: A systematic literature search was conducted to identify the relevant literature. The search period was between January 1, 2020, and September 20, 2021. The incidence of overall and various types of ocular trauma during the COVID-19 pandemic and the control period was analyzed. The data from different studies were pooled. The odds ratio (OR) and 95% confidence interval (CI) were calculated. Results: A total of 32 articles were included. After pooling the data from all included studies, the incidence of total and pediatric ocular trauma during the COVID-19 pandemic was 67.7% and 54.3% of those in the control period, respectively. However, the proportion of ocular trauma in eye emergency visits increased during the pandemic (OR, 95% CI: 1.46, 1.04–2.06). The proportion of domestic ocular trauma increased (OR, 95% CI: 3.42, 1.01–11.62), while ocular trauma related to sports and outdoor activities and occupational ocular trauma decreased (OR, 95% CI: 0.64, 0.09–4.29 and 0.18, 0.10–0.33, respectively). It was also reported that chemical injury caused by alcohol-based sanitizers, photokeratitis caused by ultraviolet lamps, and mechanical eye injury caused by masks increased during the COVID-19 pandemic. Conclusions: There was a reduction in overall eye injuries and substantial differences in the spectrum of ocular trauma during the COVID-19 pandemic. Proper health education and supervision should be strengthened to prevent ocular injuries related to COVID-19 preventive interventions.